1991
DOI: 10.1103/physreva.44.6127
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the partial decay intoH0(n’=2) by excitedH

Abstract: Two resonances in the photodetachment spectrum of H, one just below the n = 3 threshold and the other just below the n =4 threshold, were observed decaying into H {n'=2)+e. The n =3 resonance shows a preference for the n'=2 channel when compared with total-detachment measurements. Fanoline-shape fits give central energies of 12.652+0.003 eV for H * (3) and 13.338+0.004 eV for H **(4). These values are in good agreement with current theoretical calculations. PACS number(s): 32.80.Fb, 31.50.+w, 32.80.Cy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…4. If we shift the calculated resonance positions by 6 meV such that the lowest resonance coincides with the experimental value 13.338±0.004 eV [11] (the change in the lowest resonance position by the electric field is negligible), the shifted theoretical value for the third resonance is 13.511 eV which is to be compared to the experimental value of 13.513±0.001 eV. In fact, the same calculation shows that the shifted theoretical value for the second resonance position is at 13.467 eV when F=87 kV/cm, which is above the ^P^(-) potential barrier (see Fig.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…4. If we shift the calculated resonance positions by 6 meV such that the lowest resonance coincides with the experimental value 13.338±0.004 eV [11] (the change in the lowest resonance position by the electric field is negligible), the shifted theoretical value for the third resonance is 13.511 eV which is to be compared to the experimental value of 13.513±0.001 eV. In fact, the same calculation shows that the shifted theoretical value for the second resonance position is at 13.467 eV when F=87 kV/cm, which is above the ^P^(-) potential barrier (see Fig.…”
mentioning
confidence: 84%
“…4 provide the basis for our interpretation of the experimental data of Halka et al [8]. Earlier studies [9][10][11] have shown that in the zerofield photoabsorption of H~ only states of the ^P^(+) channel are populated. The potential curve for this channel, as shown in Fig.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Resonances of the type A ¼ À1 have never been observed below H thresholds with n > 2: It is predicted that they are both weaker and much narrower than the corresponding A ¼ þ1 resonance. Halka et al (1991) used photoelectron spectroscopy to study the partial decay of Feshbach resonances lying below the H(n=3,4) thresholds into the H(n=2)+e À continuum.…”
Section: Article In Pressmentioning
confidence: 99%